Desentralisasi Fiskal dan Pengaruhnya Terhadap Pertumbuhan Ekonomi di Provinsi Yogyakarta - Suciayu, Dwi; Wibawa, Fahmi (Signifikan: Jurnal Ilmu Ekonomi, 2012)
Purpose of this study is to analyze the effect of fiscal decentralization to economic growth in The Special Region of Yogyakarta Province. The Explanatory variables is local district government’s budget in terms of acceptance of revenue, revenue-sharing, the general allocation fund, and special allocation funds to economic growth in the province. The result show fiscal decentralization contributes effect to economic growth. Yet, Each variable point out that foreign-source revenue significant to influence economic growth, revenue-sharing significant effect on economic growth, the general allocation fund a significant effect on economic growth, the special allocation fund doesn’t give significant effect on economic growth. This means the implementation of fiscal decentralization has positive influence on economic growth. Thus, the central government may continue in implement fiscal decentralization in a special area of Yogyakarta since the policy could promote economic growth in the region.DOI: 10.15408/sjie.v1i1.2593